SOLVING LINEAR PROGRAMMING PROBLEMS VIA WEIGHTED LEAST-SQUARES METHOD - Übi, Evald; Übi, Jaan (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The Gaussian elimination method is usually used for solving problems related to linear programming. The paper describes an approximate method which solves a non-negative least-squares (NNLS) problem. The presented method is especially suitable for degenerate and unstable problems and also when a feasible initial solution is not known. The main ideas are explained by simple examples.m designed to fit the model was used in analysis. We also show that the DPLNM model is relatively robust to the form of prior used from the MCMC output.